1998
DOI: 10.1210/jcem.83.7.4949
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl-l-Cysteine Inhibits Apoptosis in Human Male Germ Cellsin Vitro1

Abstract: Antioxidant defenses play a critical role in the regulation of programmed cell death, even when death is induced by nonoxidative stimuli. During spermatogenesis, most of the testicular germ cells degenerate by an apoptotic process that is under hormonal control. However, the exact mechanisms by which hormonal signals are transduced within the cells to direct their life, and whether other effectors of the apoptotic pathway, for example antioxidants, take part in the control of human germ cell survival, are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…However, the improvement in sperm maturation in this group when compared with cyclophosphamide-treated group shows that N-acetylcysteine could play a substantial role in germ cell survival. This follows a report by Erkkilä et al (1998) that N-acetylcysteine plays an important role in germ cell survival in human seminiferous tubules in an in-vitro study.…”
Section: Discussionsupporting
confidence: 85%
“…However, the improvement in sperm maturation in this group when compared with cyclophosphamide-treated group shows that N-acetylcysteine could play a substantial role in germ cell survival. This follows a report by Erkkilä et al (1998) that N-acetylcysteine plays an important role in germ cell survival in human seminiferous tubules in an in-vitro study.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, NAC plays an important role in the survival of the germ cells of human seminiferous tubules in vitro (Erkkilä et al, 1998;Oeda et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…NAC conduces to the synthesis of glutathione (GSH) (Rushworth & Megson, 2014) and may help restore the depleted pool of GSH caused by OS and inflammation (Shimamoto et al, 2011;Wang et al, 2014). Some studies have reported that NAC had free radical scavenging activity both in vivo and in vitro (Ciftci et al, 2009;Erkkilä et al, 1998;Oeda et al, 1997). Safarinejad et al indicated that NAC orally daily can significantly improve sperm motility compared with placebo (Safarinejad & Safarinejad, 2009).…”
mentioning
confidence: 99%
“…The aberrantly high level of ROS has detrimental consequences on cell viability through extensive damage of DNA, proteins and organelles [29]. Antioxidant Nacetyl-L-cysteine (NAC) was considered as an important molecule of antioxidant defense for cellular resistance to exogenous stress [30,31]. Thus, antioxidant N-acetyl-Lcysteine (NAC) was employed as positive control to verify whether creatine could maintain hypoxic TNBC cell survival.…”
Section: Intracellular Creatine Enhances Cell Survival Via Activation Of Akt-erk1/2 Signalingmentioning
confidence: 99%